PEMBERDAYAAN KELUARGA DALAM PEMANTAUAN NUTRISI IBU HAMIL SEBAGAI UPAYA PENCEGAHAN KEK DALAM KEHAMILAN - Hardaniyati Hardaniyati; Irni Setyawati; Dian Soekmawaty Riezqy Ariendha (Institut Kesehatan Yarsi Mataram, 2026)
Chronic Energy Deficiency (CED) among pregnant women remains a significant health problem that increases the risk of pregnancy complications, childbirth problems, and low birth weight infants. Family members, especially husbands, play an essential role in supporting the nutritional needs of pregnant women as an effort to prevent CED. This community service activity aimed to improve the knowledge and skills of families in monitoring maternal nutrition in the working area of Sengkol Public Health Center. The methods used included health education, interactive discussions, nutrition monitoring demonstrations, and the distribution of educational media such as leaflets and daily food intake monitoring sheets for pregnant women. The participants consisted of pregnant women and their family members. The results showed an improvement in family understanding regarding the definition, risk factors, impacts, and prevention of CED during pregnancy. Families also demonstrated increased skills in monitoring maternal dietary patterns and supporting the consumption of nutritious foods and iron supplementation tablets. This activity had a positive impact on family involvement in maintaining the nutritional status of pregnant women and is expected to become an effective strategy for preventing CED in the community. Continuous educational programs and assistance from health workers are needed to strengthen the role of families in supporting maternal health.